2011
DOI: 10.1148/radiol.11110150
|View full text |Cite
|
Sign up to set email alerts
|

Color and Power Doppler US for Diagnosing Carpal Tunnel Syndrome and Determining Its Severity: A Quantitative Image Processing Method

Abstract: Color Doppler US can be used to accurately diagnose CTS. By processing the recorded power Doppler images and determining the number of pixels in the intraneural vascular area, the severity of CTS can be assessed. 2011 SUPPLEMENTAL MATERIAL: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11110150/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 33 publications
3
105
1
1
Order By: Relevance
“…To date, IVUS has not been studied extensively in entrapment neuropathies. Only 5 research groups have described IVUS in median nerve entrapment using CD imaging or power Doppler techniques 4, 10–14. No prior studies have assessed IVUS in patients with UNE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, IVUS has not been studied extensively in entrapment neuropathies. Only 5 research groups have described IVUS in median nerve entrapment using CD imaging or power Doppler techniques 4, 10–14. No prior studies have assessed IVUS in patients with UNE.…”
Section: Discussionmentioning
confidence: 99%
“…Increased intraneural vascularization detected by ultrasonography (IVUS) in peripheral nerves has not yet been studied extensively in pathologic conditions. A number of investigators have reported on IVUS in median nerve entrapment using color Doppler (CD) imaging or power Doppler techniques 4, 10–14…”
mentioning
confidence: 99%
“…Color flow in the nerve indicates hypervascularity, which at this time is graded somewhat subjectively. A recent study introduced an image-processing method for quantifying the degree of intraneural vascularity and found that the degree of measured intraneural vascularity correlated highly with the severity of the condition, according to electrodiagnostic testing [18]. …”
Section: Ultrasound Measurementsmentioning
confidence: 99%
“…In this study, the diagnosis was confirmed by using US examination in 31% of the cases with normal electrodiagnostic test findings [34]. The architectural alterations of the nerve studied by US precede conduction abnormalities in the early stages of nerve damage.…”
Section: Carpal Tunnel Syndromementioning
confidence: 68%